Phytochemical screening, phenolic compounds, antioxidant, and antibacterial activities of Zizyphus lotus from Beni Mellal region, Morocco - Zazouli, Sofia (Acta Scientiarum. Biological Sciences, 2025)
The study thoroughly investigated the phytochemical composition, antioxidant, and antibacterial properties of Zizyphus lotus extracts from leaves, seeds, pulps, and root barks. Analysis revealed a diverse range of phytochemicals, with polyphenols, flavonoids, mucilage, gallic tannins, and catechic tannins being predominant. Highest total phenolic content was observed in leaves, followed by root barks and seeds, while root barks had the highest total anthocyanin content. Antioxidant assays (DPPH, ABTS, and FRAP) demonstrated robust activity in all extracts, notably in root bark (IC50 = 5.97 µg mL-1) and leaf (IC50 = 9.68 µg mL-1) extracts, surpassing the potency of BHT (IC50 = 11.30 µg mL-1). Moreover, extracts exhibited significant antibacterial activity against Escherichia coli, Methicillin-Sensitive Staphylococcus aureus (MSSA), and Methicillin-resistant Staphylococcus aureus (MRSA) at concentrations of 1024 and 2048 µg/mL, with leaves and root barks showing the strongest effects. Staphylococcus epidermidis displayed the highest resistance. Such findings not only deepen our understanding of Zizyphus lotus but also pave the way for leveraging its pharmacological benefits in pharmaceuticals, nutraceuticals, and functional foods.